Al-Tsabit Wa Al-Mutahawwil, Adonis Dan Kritik Terhadap Kejumudan Budaya Arab Islam - Nanang Abdillah (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2011)
This article seeks to provide a theoretical concept of how to understand Adonis thought. Historical analysis, combine with literary overview, is deployed to trace the empirical passage of Adonis thought al-Tsabit wa al-Mutahawwil concept. This article argues that al-Tsabit wa al-Mutahawwil is the new concept for Arabs cultural studies. Following this process, the concept of al-Tsabit wa al-Mutahawwil have been found the two mindstream in the Arab world, aql (rational) and naql (text). Keywords: Sastra Arab, kebudayaan, al-Tsabit wa al-Mutahawwil